Conserving apollo butterflies: habitat characteristics and conservation implications in Southwest Finland - Kukkonen, Jonna M.; von Numers, Mikael; Brommer, Jon E. (Springer Dordrecht, 2025)
The conservation of insects, particularly endangered species such as the Apollo butterfly, is a pressing global concern. Understanding the habitat requirements and factors influencing species occupancy is crucial for designing effective conservation strategies. We focused on investigating the habitat characteristics expected to affect the occupancy of the nationally endangered Apollo butterfly in Southwest Finland. We conducted field surveys and GIS analysis to assess the impact of larval host plant and adult nectar resources, habitat encroachment, elevation, connectivity, and spatial variation on Apollo larval occupancy in rocky outcrop habitats. We found that rocky outcrops with abundant host plants and those less isolated from nectar patches play a significant role in supporting Apollo reproduction, whereas encroachment, specifically increased tree volume, negatively affected occupancy. We additionally observed spatial variation in occupancy across different blocks within the study area. Our findings emphasise the importance of resource availability for Apollo butterflies and highlight the dynamic nature of their habitat requirements. Maintaining a network of intact rocky outcrops with suitable resources is essential for the long-term persistence of the Apollo butterfly population in the region.
Implications for insect conservation: Our research underscores the critical need to protect and restore habitats for the Apollo butterfly, particularly by addressing threats such as habitat encroachment and construction projects that pose risks to their breeding sites.